1970
DOI: 10.1111/j.1365-246x.1970.tb06056.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Aspects of the Earth's Non-dipole Magnetic Field over Upper Tertiary Times

Abstract: Investigation of collected palaeomagnetic results from continental igneous rocks and from oceanic sediment+ores, shows a persistent off-centre displacement of the effective dipole source of the main field over Quaternary and Recent times (about the past two million years). This dipole displacement is 191 f38 km northward along the rotational axis. Further evidence suggests a similar enduring displacement during all of Upper Tertiary time. The effect of this result on palaeomagnetic interpretations is discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
0
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(135 citation statements)
references
References 17 publications
8
126
0
1
Order By: Relevance
“…Most of the poles would still be significantly different from the geographic pole at the 95% significance level. A far sided and right handed tendency was first noted by Wilson [1970Wilson [ , 1972. The longitudinal distribution of poles from all of the latitudinal bands will be the subject of a future paper.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the poles would still be significantly different from the geographic pole at the 95% significance level. A far sided and right handed tendency was first noted by Wilson [1970Wilson [ , 1972. The longitudinal distribution of poles from all of the latitudinal bands will be the subject of a future paper.…”
Section: Resultsmentioning
confidence: 99%
“…The far-sided effect, first identified by Wilson [1970], has been attributed to the presence of a persistent axial quadrupole superimposed on the main axial dipole [Wilson, 1971] (Figure 7b and Table 5) corresponds to a lower energy spectrum [Lowes, 1974] for each degree (l = 2 to 4) of the spherical harmonic representation (Table 5; because the value of the axial dipole coefficient is set to 30 gT, the energy spectrum is not calculated for degree I = 1). The differences between the two models are more easily analyzed using the difference of the Br component at the CMB (Figure 7c).…”
Section: Implications For Taf Modelsmentioning
confidence: 99%
“…The GAD hypothesis has served as an excellent first order model, especially for the use of palaeomagnetic data in terms of continental drift (IRVING, 1964;MCELHINNY, 1973). Detailed analyses of the data covering the past few million years have shown that there are second order effects which produce significant departures from the GAD hypothesis (WILSON, 1970(WILSON, , 1971(WILSON, , 1972WILSON and MCELHINNY, 1974;Cox, 1975). MERRILL and MCELHINNY (1977) have shown that the time-averaged field is best represented by a series of zonal harmonics in a spherical harmonic expansion.…”
Section: Introductionmentioning
confidence: 99%